Analisis Tipologi Wisatawan dalam Pengembangan Ekowisata di Taman Nasional Komodo, Nusa Tenggara Timur - Felisha Amara Bahwono; I Made Bayu Ariwangsa (JURNAL DESTINASI PARIWISATA, 2022)
Komodo National Park (KNP) is one of Indonesia’s influential conservation sites that has caught thepublic’s attention due to a massive, ongoing tourism development model that contrasts ecotourism principles.Tourism developments are mostly based on potential and demands which generally stem from tourists. Byanalyzing the tourist typology of Komodo National Park, authorized stakeholders could synchronize betweenthe development model and tourists’ demands which will result in an equilibrium that supports both theconservation and tourism functions of Komodo National Park.This research uses a mixed-method, using both qualitative and quantitative approaches. The data werecollected through non-participatory observation, literature study, documentation, and online questionnaires.It uses purposive sampling with a close-ended questionnaire using the Likert Scale. The theory used in thisstudy is the Tourist Psychographic Typology.The research results indicated that aggregately, tourists’ visit rate in Komodo National Park is increasingin numbers although it is still fluctuating by nature, especially with the COVID-19 Pandemic intervention. Thisresearch also found that from a psychographic model, the majority of Komodo National Park’s tourists are inthe ‘near-allocentric’ pole. Therefore, it is concluded that the applied tourism policies should be re-evaluated tomaintain and uphold the applicable ecotourism principles.Keywords: Tourist Typology, Ecotourism, Psychographic, Conservation Tourism.